Numerical Analysis of Unsaturated Soil Slopes under Rainfall Infiltration Based on the Modified Glasgow Coupled Model - Guoqing Cai; Mengzi Li; Bowen Han; Kenan Di; Qianqian Liu; Jian Li (Advances in Civil Engineering)
An ABAQUS UMAT subroutine was used for the secondary development of the established coupled hydromechanical constitutive model of unsaturated soil considering the effect of the microscopic pore structure. Combined with Euler’s backward implicit integration algorithm, a numerical program was established for simulating the proposed model. The developed numerical program was used to simulate the rainfall infiltration process of an actual slope engineering example, and the effects of rainfall intensity and rainfall duration on the pore pressure, fluid velocity, and displacement of the unsaturated soil slope were analyzed. The results show that the developed numerical program can reasonably analyze the changes in the seepage field and displacement field of unsaturated soil slopes under rainfall infiltration.